Motivation for Distance Learning as A Factor Affecting the Quality of Education - NADTOCHIY, YULIYA B. (The journal of contemporary issues in business and government, 2021)
Online learning is becoming increasingly popular in today’s world. This can be clearly seen through the number of training courses and various training activities that are being developed and offered. At the present time, ‘distance learning’ and ‘online learning’ are often used as interchangeable terms. However, distance learning is considered to be a broader concept, it is the remote learning which is not necessarily real time learning, and online learning is learning via the Internet connection “here and now” and is considered only as one of the forms of distance learning. So, one can also note that there is an ambivalent opinion regarding distance learning: some people recognize and trust this form of learning while the others have a negative attitude towards receiving education in this way. The article shows the results of surveys conducted in different years in order to find out people’s opinions on the possibility of getting proper education through distance learning.